Rangsang Awal sebagai Motivasi dalam Pembelajaran Koreografi di Jurusan Pendidikan Sendratasik - Desfiarni Desfiarni (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
The creation of works of choreography requires a creative work process and time of development, ranging from initial stimulation until the dance composition. The stimulation of dance begins with stimulation of ideas, visual stimulation, stimulation of audio, kinesthetic stimulation, ad touch stimulation. The creation of dance associated with the creative process requires sufficient time. Choreographers are not just stringing-chain motion, but to develop ideas, creative power train in expressing movement, abstracting ideas at this stage of cultivation, improving the knowledge of understanding, and providing a variety in the creative process. Exploration activities undertaken are not yielding a form of dance, but rather motivating and stimulating the creation of a new movement through stages of composition that would be a form of dance. The appearance of creative ideas requires natural objects as the inspirations for choreographers Key word: Keyword: First stimulus, choreography, dance, choreographer, motivation.